An annotated checklist of Ciidae (Coleoptera: Tenebrionoidea) of Ukraine - Drogvalenko, Alexander; Diedus, Valeriia (Zootaxa, 2026)
The article provides an overview of Ukrainian Ciidae (Coleoptera: Tenebrionoidea). Based on the literature review and new data, 53 species from 12 genera (all from the subfamily Ciinae) are presented. Data on the trophic relationships of Ciidae with tinder fungi are provided. It is proposed to return the species Orthocis reflexicollis to the genus Cis based on the morphological similarity of the imago and larvae with this genus. For the first time in Europe and Ukraine, 2 species are noted: Cis seriaticribratus and Hadreule blaisdelli. Also, C. seriaticribratus is noted for the first time as a pest of mycological herbariums.